Hope eaudiobook A memoir of survival in cleveland. - Berry, Amanda (Penguin Audio, 2015)
Two victims of infamous Cleveland kidnapper Ariel Castro share the story of their abductions, their decade in captivity, and their dramatic escape   On May 6, 2013, Amanda Berry made headlines around the world when she fled a Cleveland home and called 911, saying: “Help me, I’m Amanda Berry. . . . I’ve been kidnapped, and I’ve been missing for ten years.”   A horrifying story rapidly unfolded. Ariel Castro, a local school bus driver, had separately lured Berry, Gina DeJesus, and Michelle Knight to his home, where he kept them chained. In the decade that followed, the three were raped, psychologically abused, and threatened with death. Berry had a daughter—Jocelyn—by their captor.   Drawing upon their recollections and the diary kept by Amanda Berry, Berry and Gina DeJesus describe a tale of unimaginable torment, and Pulitzer Prize–winning Washington Post reporters Mary Jordan and Kevin Sullivan interweave the events within Castro’s house with original reporting on efforts to find the missing girls. The full story behind the headlines—including details never previously released on Castro’s life and motivations— Hope is a harrowing yet inspiring chronicle of two women whose courage, ingenuity, and resourcefulness ultimately delivered them back to their lives and families. Read by Jorjeana Marie, Marisol Ramirez, and Arthur Morey.